Combined effect of a farnesoid X receptor agonist and dipeptidyl peptidase‐4 inhibitor on hepatic fibrosis. Issue 10 (15th July 2019) - Shimozato, Naotaka; Namisaki, Tadashi; Kaji, Kosuke; Kitade, Mitsuteru; Okura, Yasushi; Sato, Shinya; Moriya, Kei; Seki, Kenichiro; Kawaratani, Hideto; Takaya, Hiroaki; Sawada, Yasuhiko; Saikawa, Soichiro; et al.
Abstract : Aim: Non‐alcoholic steatohepatitis (NASH) has a broad clinicopathological spectrum (inflammation to severe fibrosis). The farnesoid X receptor agonist obeticholic acid (OCA) ameliorates the histological features of NASH; satisfactory antifibrotic effects have not yet been reported. Here, we investigated the combined effects of OCA + a dipeptidyl peptidase‐4 inhibitor (sitagliptin) on hepatic fibrogenesis in a rat model of NASH. Methods: Fifty Fischer 344 rats were fed a choline‐deficient L‐amino‐acid‐defined (CDAA) diet for 12 weeks. The in vitro and in vivo effects of OCA + sitagliptin were assessed along with hepatic fibrogenesis, lipopolysaccharide–Toll‐like receptor 4 (TLR4) regulatory cascade and intestinal barrier function. Direct inhibitory effects of OCA + sitagliptin on activated hepatic stellate cells (Ac‐HSCs) were assessed in vitro . Results: Treatment with OCA + sitagliptin potentially inhibited hepatic fibrogenesis along with Ac‐HSC proliferation and hepatic transforming growth factor (TGF)‐β1, α1(I)‐procollagen, and tissue inhibitor of metalloproteinase‐1 (TIMP‐1) mRNA expression and hydroxyproline levels. Obeticholic acid inhibited hepatic TLR4 expression and increased hepatic matrix metalloproteinase‐2 expression. Obeticholic acid decreased intestinal permeability by ameliorating CDAA diet‐induced zonula occludens‐1 disruption, whereas sitagliptin directly inhibited Ac‐HSC proliferation. The in vitro suppressive effects of OCA + sitagliptin on TGF‐β1 and α1(I)‐procollagen mRNA expression and p38 phosphorylation in Ac‐HSCs were almost consistent. Sitagliptin directly inhibited the regulation of Ac‐HSC. Conclusions: Treatment with OCA + sitagliptin synergistically affected hepatic fibrogenesis by counteracting endotoxemia induced by intestinal barrier dysfunction and suppressing Ac‐HSC proliferation. Thus, OCA + sitagliptin could be a promising therapeutic strategy for NASH.